CASE Technologies (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In three articles, the term "CASE" (Computer Aided Software Engineering) is defined in a very broad sense, and the original meaning of the term CASE has now acquired a new meaning that interrupts the production process of complex IT. information about.